Energy Harvesting System with Solar Panels to Supply Low Power Electronic Devices - Cumbajín, Myriam (2023)
Solar panels allow acquiring energy from the environment which can be stored for Energy Harvesting purposes. The objective of this work is to design, simulate and characterize different configurations in the harvesting stage, constituted by solar panels for energy harvesting systems of low consumption, identifying the most adequate arrangement to achieve the highest amount of energy together with the conversion stage. The methodology used has been design, simulation in Matlab-Simulink software and characterization with mini solar panels. The developed system consists of 3 stages which are: energy harvesting, DC-DC converter, and storage, focusing on the Energy Harvesting stage. The results obtained in simulation of 4.8V and 160 mA, and measurement of 4.60V and 134.5mA show that the mixed configuration is the one that presents better results in both voltage and current, concluding that the simulated and measured values are very close obtaining an error of 0.05% and 0.16% in voltage and current respectively and an output voltage of the converter of up to 26V. Finally, these results are very promising for Energy Harvesting applications.